Near-ultraviolet continuum modeling of the 1985 April 12 great flare of AD Leo - Adam F. Kowalski; Adam F. Kowalski; Adam F. Kowalski (Frontiers in Astronomy and Space Sciences, 2022)
White-light stellar flares are now reported by the thousands in long-baseline, high-precision, broad-band photometry from missions like Kepler, K2, and TESS. These observations are crucial inputs for assessments of biosignatures in exoplanetary atmospheres and surface ultraviolet radiation dosages for habitable-zone planets around low-mass stars. A limitation of these assessments, however, is the lack of near-ultraviolet spectral observations of stellar flares. To motivate further empirical investigation, we use a grid of radiative-hydrodynamic simulations with an updated treatment of the pressure broadening of hydrogen lines to predict the λ ≈ 1800 − 3300 Å continuum flux during the rise and peak phases of a well-studied superflare from the dM3e star AD Leo. These predictions are based on semi-empirical superpositions of radiative flux spectra consisting of a high-flux electron beam simulation with a large, low-energy cutoff (≳ 85 keV) and a lower-flux electron beam simulation with a smaller, low-energy cutoff (≲ 40 keV). The two-component models comprehensively explain the hydrogen Balmer line broadening, the optical continuum color temperature, the Balmer jump strength, and the far-ultraviolet continuum strength and shape in the rise/peak phase of this flare. We use spatially resolved analyses of solar flare data from the Interface Region Imaging Spectrograph, combined with the results of previous radiative-hydrodynamic modeling of the 2014 March 29 X1 solar flare (SOL20140329T17:48), to interpret the two-component electron beam model as representing the spatial superposition of bright kernels and fainter ribbons over a larger area.